O Grupo Vriesea platynema Gaudich. (Tillandsioideae, Bromeliaceae) no Estado do Paraná: aspectos taxonômicos e anatômicos - Kowalski, Vanessa Koza (2013)
Bromeliaceae Juss. is essentially neotropical, represented by 58 genera and about 3.172 species, being Brazil its largest center of diversity, with 42 genera, 17 are endemics, and 1.200 species, occurring in all biomes, with the highest species richness locates on the coast east, the Atlantic Forest. Evolutionary aspects as the capture and storage of water by leaves arranged in a rosette, forming a tank, and the absorption of water and nutrients through the trichomes, possible life in extreme environments and diverse, contributing to the wide distribution of this family, and generate conditions necessary for the survival of many organisms from their leaves. The family is subdivided into eight subfamilies: Brocchinioideae Givinish, Lindmanioideae Givinish, Tillandsioideae (Dumortier) Harms, Hechtioideae Givinish, Navioideae Hams, Pitcairnioideae (Meisner) Harms, Puyoideae Givinish and Bromelioideae. Vriesea Lindl. belongs to the Tillandsioideae, with 261 species, distributed predominantly in South America. The genus has groups of species, difficult delimitation among them, the complex Vriesea platynema Gaudich. with 41 species. This occurs from Central America to Argentina, with a strong polymorphism, leading the erroneous identification of taxa. Based on material in vivo and herbarium collections, a taxonomic study was conducted in the state of Paraná. Three taxa were recognized: Vriesea platynema Gaudich. var. platynema, widely distributed taxon classified as not threatened (LC) according to the criteria established by IUCN, Vriesea platynema var. variegata (Guillon) Reitz, endemic to the Paraná and classified as Endangered (EN), by its reduced extent of occurrence, and Vriesea tijucana E. Pereira, as endangered (EN), being restricted to FOD, present few points of occurrence, which are located in protected areas or in urban development. Descriptions, comments, key identification, geographical distribution, conservation status and illustrations are presented. In parallel, an anatomical study of the vegetative organs was performed, where we tried to identify anatomical features with taxonomic value, and check the adaptations to the habitat of each taxon. The three taxa analyzed have absorptive and grampiformes roots, tank well developed and specialized trichomes, mainly C3 metabolism and the epiphytic habit.